Impact of biopsychosocial education on the quality of life of the elderly: systematic review (Research, Society and Development, 2023)
This study aimed to carry out a systematic review on the impact of biopsychosocial education on the quality of life of the elderly. Thus, we sought to conceptualize this type of education, already mentioned, as those activities developed with the purpose of encouraging and promoting health, preventing the appearance and development of the disease. In this sense, a systematic review was carried out, following the norms of the PRISMA declaration, to answer the guiding questions mentioned in the introduction of the present study. For the results, twenty published works were considered (1 article, in 2018; 2 in 2019; 1 in 2020; 1 in 2021 and 15 in 2022) that address interventions with the elderly in the various physical, psychological, social, cultural and environmental factors that demonstrate the findings of the present study. Therefore, it is possible to conclude that the provision of biopsychosocial education, carried out systematically, benefits and empowers the elderly; thus reflecting a great benefit to society, health and quality of life for this public.